Location Quotient Analysis to Facing Competition in The Pandemic Era Of Covid-19 (Case Study: East Java Province) - Lienggar Rahadiantino; Juniarun Fathurrohman (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2021)
The COVID-19 pandemic has had a significant impact on the order ofpeople's lives. Apart from the health sector, the economic sector is alsoaffected so that a balanced and well-targeted policy is needed to overcomethis impact. Large-Scale Social Restrictions (PSBB) which wereimplemented to reduce the rate of transmission of COVID-19 causeseconomic activity, both production, consumption and distribution to behampered, causing an economic contraction. The national economycontracted by 5.32 percent (y-o-y) and the economy of East Java contracted5.90 percent (y-o-y) in the second quarter of 2020. Even so, there are severaleconomic sectors that still have good performance and have contributedgreatly to East Java's Gross Regional Domestic Product. Using of LocationQuotient (LQ) analysis in this study aims to identify basic sectors andformulate the composition and shift of the basic sectors by using GRDP asan indicator of regional growth.